Metabolic and molecular mechanisms underlying the foliar Zn application induced increase of 2-acetyl-1-pyrroline conferring the ‘taro-like’ aroma in pumpkin leaves - Deng, Liting; Yang, Xian; Qiu, Yuehan; Luo, Jianning; Wu, Haibin; Liu, Xiaoxi; Zhao, Gangjun; Gong, Hao; Zheng, Xiaoming; Li, Junxing (Frontiers in Plant Science, 2023)
Introduction Fresh pumpkin leaf is popular vegetable for its rich nutrition. The pleasant taro-like odour is important aroma quality of crops, and mostly contributed by 2-acetyl-1-pyrroline in pumpkin. Element Zn can impact metabolite biosynthesis in plants, including aroma formation. However, Zn-induced biochemical responses, especially 2-acetyl-1-pyrroline formation in pumpkin, haven’t been elucidated. Methods This study integrated metabolome and transcriptome to explore molecular fluctuations in pumpkin leaves at different time intervals after foliar Zn treatment. Result and Discussion We first identified more than one thousand metabolites from pumpkin leaves by integrating different mass spectrometry methods according to the form in which a metabolite exists. Comparative metabolomic analysis revealed there were separately 25 out of 50 and 286 out of 963 metabolites that were respectively identified by gas chromatography-mass spectrometry and liquid chromatography-tandem mass spectrometry, differentially regulated by Zn treatment. Our findings revealed that 50mg/L of Zn significantly enhanced 2-acetyl-1-pyrroline production by more than 38%, which was contributed by increased biosynthesis of its precursors, including ornithine and proline. The following transcriptome analysis discovered 30,574 genes, including 953 novel genes. Zn treatment induced the differential expression of 41.6% of identified genes which were supposed to regulate the downstream metabolite changes in a time-dependent manner. Pathway analysis indicated that alternations in primary metabolism, including carbon metabolism and biosynthesis of amino acids, were vital to the fluctuated aromatic compound generation. Phytohormones and transcription factors may regulate the expression of gene P5CS and proline biosynthesis, which, therefore, affect 2-acetyl-1-pyrroline production. This research reveals molecular mechanisms of 2-acetyl-1-pyrroline formation in pumpkin, which will provide the molecular basis for desired aroma compound production through metabolite engineering.